Rapid direct conversion of bovine non-adipogenic fibroblasts into adipocyte-like cells by a small-molecule cocktail - Sun, Longfei; Zhang, Dandan; Qin, Liangshan; Liu, Quanhui; Wang, Guodong; Shi, Deshun; Huang, Ben (Frontiers in Cell and Developmental Biology, 2023)
The molecular regulation mechanism of fat deposition in bovine and its improvement on beef quality are important research directions in the livestock industry. Direct conversion of non-adipogenic bovine fibroblasts into functional adipocytes by transdifferentiation techniques can be used for research adipocyte deposition of bovine. Here we describe a rapid strategy for transdifferentiation of bovine ear fibroblasts(BEFs) into adipocyte-like cells by using a small-molecule cocktail (10μM RepSox, 500ug/mL VPA, 1μM TTNPB). In this study, the chemically-induced adipocytes (CiADCs) could be identified as early as day 6. The CiADCs appeared to be circular and rich of lipid droplets. Adipocyte-specific genes were significantly expressed in CiADCs. In addition, we also found that the signaling pathways (PPAR signaling pathway, PI3K-Akt signaling pathway, p53 signaling pathway, MAPK signaling pathway and ECM-receptor interaction) regulated by the DEGs played a vital role in adipogenesis. We further observed that the signaling pathways regulating of adipogenic differentiation had been turned on after 3 days of induction by Gene set enrichment analysis (GSEA). These findings may offer a new insight to increasing the amounts of adipocytes in the beef to improve the meat quality and underlines the key signaling pathways that are needed to induce adipocyte.